PENGARUH PENYULUHAN KESEHATAN TENTANG SADARI TERHADAP PENINGKATAN PENGETAHUAN PADA REMAJA PUTRI DI PONPES NURUL HIKMAH KABUPATEN TEGAL - Fadilah, Ayu; Romdiyah, Romdiyah; Purnamasari, Ika; Khoiriyah, Siti (Jurnal Ilmiah Kesehatan, 2025)
Background: cancer is a disease characterized by the uncontrolled development of abnormal cells that have the ability to move between cells and body tissues. Breasts are a significant global problem, especially in indonesia. Adolescent girls often have minimal information about breast cancer and carry out breast self-examination (bse). The lack of numbers leads to low bse practice among adolescent girls, even though this method is effective for early detection of breast cancer. Objective: this study aims to determine the effectiveness of health education on breast self-examination or awareness on increasing knowledge among them. Method: this research uses quantitative methods, with a pre-experimental design, one group pre-test and post-test. The population in this study was 40 young women at the nurul hikmah islamic boarding school, tuwel village, tegal regency, the sample was selected with Results: this study concluded that health education about breast self-examination (bse) influence on increasing knowledge in young women with asymp scores. Sig. (2-tailed) of 0,000. Conclusion: Health education about sadari influences the level of knowledge in adolescents.